Analysis of Factors Associated with Measles Rubella (MR) Immunization in Toddlers Aged 9-24 Months at the Kedungwuni II Community Health Center, Pekalongan Regency - Chairiza Paundrian Negari; Slamet Budiyanto; Jaya Maulana (Jurnal Kesmas Prima Indonesia, 2026)
Measles and rubella remain a public health problem due to the high risk of transmission and complications in toddlers. This study aims to analyze the relationship between predisposing factors (maternal knowledge and attitudes), supporting factors (access to health facilities), and motivating factors (family support, support from health workers, and information from health workers) with the provision of Measles Rubella (MR) immunization to toddlers aged 9–24 months. The study used a quantitative method with a cross-sectional design. The population was 677 mothers with toddlers aged 9–24 months in the working area of ​​the Kedungwuni II Community Health Center, Pekalongan Regency, with a sample of 87 respondents selected using a stratified random sampling technique. Data were collected through questionnaires and analyzed using the Chi-Square and Fisher Exact tests at a significance level of 5%. The results showed that maternal attitudes, access to health facilities, family support, support from health workers, and information from health workers had a significant relationship with the provision of MR immunization, while maternal knowledge level did not have a significant relationship. This study emphasizes the importance of strengthening education, family support, and easy access to immunization services as an effort to increase MR immunization coverage in toddlers.